A PRODUÇÃO CAMPONESA E O MONOPÓLIO DO TERRITÓRIO PELO CAPITAL: ESPACIALIDADES DISTINTAS NA EXTRAÇÃO DA ERVA-MATE NA REGIÃO DA FLORESTA COM ARAUCÁRIA DO PARANÁ - Barreto, Marcelo (2008)
The present work aim to propose a comprehension about the peasantry production on the Araucaria Forest region of Parana nowadays, precisely the one known as Faxinal System. The Faxinais peasantry organization consolidated on the half part of the XIXth century, when the economical activity of the mate herb production started to increase on the state. Among this period, several manufacturing industrial units started to appear next to the coast and around the city of Curitiba. Those industries used to obtain from those peasants the mate herb primary manufactured as raw material to feed their production faced to overseas market. Due to this activity crisis, during the dacade of 1930, provoked by the increase of the mate herb production in Argentina, the biggest market for the brazilian mate herb, those faxinais communities started to orginize into several cooperatives. The mate cooperatives on the region lasted till the half of the 80`s, when a new crisis took place, this time provoked by the closure of the uruguaian market. Whe the mate herb production reestarded its productin with significative levels, the mate herb industries decided to realocate their manufacturing plants. This time, together with the raw material on the Center-south of Parana. From this time on, those factories did no obbtained the pimary manufactured mate herb from the peasants anymore, but the green leaf for the total manufacturing inside the industrial process. This way, it was retired from peasantry hands the possibility of the obbtainance of income. With the accsition of the green leaf and not primary manufactured, the mate herb industrial capital finds a possibility of reproduction in peasantry lands through the territory monopolization. This way, distincts spatialities are been created on the Faxinals territory. Through the process of fighting and resistance on their land, the Faxinais do not dissolve and keep reproducting as peasants till nowadays.